Exploration of Xanthone Derivatives as Anti-Cancer Agents against Colorectal Cancer - Miladiyah, Isnatin (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Colorectal cancer currently occupies the third position of globally cancer morbidity and is the second leading cause of cancer death after lung cancer. Chemotherapy administration is still the main modality for the colorectal cancer stage I to III. Its usage is limited, since its high resistance and risk of side effects. Thus, exploration and development of novel colorectal anti-cancer drugs, including compounds derived from nature origin is needed. Xanthone becomes one natural compound which may be potentially developed as an anti-colorectal cancer due to its cytotoxic and anti-proliferative activities. The in vitro cytotoxic and anti-proliferative actions of xanthone compounds occur through a variety of mechanisms involving both apoptotic induction and inhibition of cell cycle, while in vivo may reduce the tumor size. Since colorectal cancer is frequently treated in a combination therapy, xanthone compounds have also been studied in a combination use and proven effective as co-chemotherapy with the standard chemotherapy drugs. This paper aims at providing an overview of colorectal cancer, pathology, risk factors and protective factors, as well as discussing the current therapies and potential xanthone compounds as an alternative therapy which may be developed later for the colorectal cancer